Evaluation of charging infrastructure for electric trucks in the European Union: Navigating the Electrified Road: A Systematic Literature Review of Electric Truck Infrastructure in Europe - Olevic, Kenan; Peshevski, Antonijo (My University, 2024)
The European Green Deal establishes ambitious climate objectives, including adopting electric trucks as a crucial element in reducing emissions within the transportation industry. An essential aspect of this shift is the requirement for a robust and reliable charging infrastructure to facilitate extensive adoption throughout the European Union. This study investigates the requirements and barriers related to adopting electric trucks for long-haul transport in the European Union. To achieve this result, a systematic literature review was conducted. The result shows that for the implementation of electric trucks for long-haul in the EU, the battery capacity, the charging technology, and a massive buildup of charging infrastructure are crucial for the transition. Furthermore, the difference in initial investment for acquiring an electric truck and a diesel truck is still significant. To overcome these obstacles, policymakers and industry players must work together in a coordinated manner. Strategic investments in infrastructure and the creation of a new legal framework in favor of transport companies can improve the shift to electric trucks, which aligns with the climate goals of the European Union and promotes a sustainable future for transporting goods. It is essential to mention that the study does not consider social sustainability and energy demand.
Keywords: Battery; electric; truck; charging; infrastructure; EU; requirements; barriers; implementation